Effects of repeat exposure to inhalation anesthetics on liver and renal function - Tomoki Nishiyama (Wolters Kluwer Medknow Publications, 2013)
Background: Cross hypersensitivity to inhalation anesthetics has not been studied. The aim of this study was to investigate it by comparing liver and renal function after repeated anesthesia with sevoflurane and isoflurane retrospectively. Materials and Methods: The adult patients who received general anesthesia twice within the interval of 14 days to 1 year were retrospectively analyzed. Those who received sevoflurane anesthesia twice (SS group, 53 cases), isoflurane anesthesia twice (II group, 31 cases), sevoflurane followed by isoflurane anesthesia (SI group, 29 cases), isoflurane followed by sevoflurane anesthesia (IS group, 35 cases), and propofol-fentanyl anesthesia twice (PP group, 58 cases) were enrolled. Serum concentrations of aspartate aminotransferase (AST), alanine aminotransferase (ALT), total bilirubin (Bil), gamma-glutamyl transpeptidase (γ-GTP), blood urea nitrogen (BUN), and creatinine (Cr) measured 1-3, 5-8, and 12-16 days after surgery were investigated. Results: In the IS group, the number of the patients with abnormal values of ALT and γ-GTP 5-8 days after surgery were significantly smaller at second anesthesia compared to the first anesthesia. The number of the patients with abnormal values of AST, ALT, and γ-GTP were significantly larger in the II group than the SS and PP groups. The number of patients who had higher values in each parameter at second anesthesia compared to the first anesthesia was not different among the groups. Conclusions: Sevoflurane and isoflurane might have no cross hypersensitivity. Both anesthetics might not have any additional risks to increase liver and renal damage by second anesthesia.